The Influence of Leadership Behavior and Employee Commitment to Work Performance of Multi Nabati Sulawesi Corporation - Delva Monoarfa; Tinneke E.M. Sumual; Marice P. Legi (Journal of International Conference Proceedings (JICP), 2021)
This study aims to analyze the influence of leadership behavior and employee commitment to work performance of employees in Maleo Unit Multi Nabati Sulawesi Corporation. The company faces the challenge of how to improve the work performance of employees. The method used in this research is quantitative research methods. The data collection techniques using a questionnaire distributed to 94 employees who work in the company. This study consist of three variable Leadership behavior is measured by the ability to motivate, direct, communicate, decision-making, and responsibility. Employee commitment is measured by acceptance of organizational objectives, loyalty, compliance with organizational rules, work engagement, and acceptance of organizational values. Work performance is measured by cooperation, creativity, time utilization, quality of work, and quantity of work. The data was analyzed using multiple regression analysis techniques. The results of the analysis are known that the value of 9.19 where is the value of F_test > F_tabel or 9,190 > 3,097, with a significant rate of 0.00 which means less than 0.05 or 0.00 < 0.05. This means there is a simultaneous influence between leadership behavior and work commitment to the work performance of employees in Maleo unit Multi Nabati Sulawesi Corporation.